Microwave Assisted Selective Synthesis of four Chromanones Via Biscyclization Method in the Presence of Polyphosphoric Acid and Crystal Structure Determination of Their Dicarboxylic Acids - Abbas Shockravi; Robabeh Alizadeh; Hossein Aghabozorg; Leyla Hossein Mohebbi; Saeed Moradi Koochi; Abolghasem Moghimi (Iranian Journal of Chemistry & Chemical Engineering, 2004)
Microwave irradiation is used in the synthesis of four tricyclic chromanones 11-14. The chromanone 14 and 12 are selectively formed thermally and under microwave in the presence of polyphosphoric acid (PPA) from the same dicarboxylic acid 9, respectively. The crystal structures of the two diacids are also reported. The corresponding ortho and meta isomers of diacids crystallize in the space group Pbca of the orthorhombic system and C2/c of the monoclinic system respectively, with 8 and 4 molecules in the unit cells of dimensions a = 4.9955(1) Å and 4.8092(4) Å; b = 19.177(4) Å and 11.5609(1) Å; c = 25.885(5) Å and 21.247(2) Å; α = 90˚ and β = 91.214(3)˚ respectively. The structures have been refined to final values for the crystallographic R factors of 0.0401 and 0.0247, based on 2146 and 1030 observed independent reflections, respectively.